JURNAL AKUNTANSI MULTIPARADIGMA : Tinjauan Konseptual: Criteria Supplier-Selection, Integrasi Internal dan Eksternal Supply Chain terhadap Kinerja Perusahaan - Endar Pituringsih (Fak. Ekonomi dan Bisnis Universitas Brawijaya, 2010)
Performance measurement reflects the company capability to prepare for the customer desired standard while it considers lower production and maintenance costs, higher product quality, reduced stock in process, deprived material processing cost, and shorter delivery deadline. Meanwhile, Supply Chain Management (SCM) has important meaning to empower consumer in maximizing customer value. Supply Chain Management (SCM) requires: internal integration (intra-organization) and external integration (inter-organization). Primary key of Supply Chain Management (SCM) will be having supplier as partner in the company strategy and satisfying the always changing market demand. Therefore, a selection among company strategy options in the global competition really produces a model of dominant integration, coordination, and cooperation in controlling global market, precisely through supply chain as important element to contribute to company performance improvement.